HUBUNGAN JUMLAH LEUKOSIT DENGAN GANGGUAN FUNGSI EKSEKUTIF PADA CEDERA KEPALA RINGANSEDANG - Gilbert Tangkudung,* Junita Maja PS,* Herlyani Khosama* (NEURONA, 2016)
INTRODUCTION IN TRAUMATIC BRAIN INJURY THERE ARE FEW FACTORS THAT CAN AFFECT THE OUTCOMES SUCH AS INFLAMMATION INDICATED BY LEUKOCYTE COUNTS TRAUMATIC BRAIN INJURY IMPACTS ARE VERY DIVERSE FROM MOTOR AND SENSORY IMPAIRMENT TO COGNITIVE IMPAIRMENT ESPECIALLY EXECUTIVE FUNCTION THAT CAN AFFECT THE QUALITY OF LIFE